Feasible electricity price calculation and environmental benefits analysis of the regional nighttime wind power utilization in electric heating in Beijing. (1st March 2019) - Pu, Lei; Wang, Xiuhui; Tan, Zhongfu; Wu, Jing; Long, Chengfeng; Kong, Weizheng
Abstract: Facing the aggravation of air pollution and serious wind curtailment in North China, a new way to utilize excess wind power is presented, which is to use the excess nighttime wind from the surrounding areas to provide electric heating in Beijing at night. First, the mechanism of the nighttime electric heating price calculation and its environmental benefits are explained from both the supply side and the demand side. Second, considering the economic and environmental characteristics of electric heating, the electricity price-ceiling calculation model on the demand side, the electricity price-floor calculation model on the supply side, and the environmental benefit-analysis model are formed. Finally, the models are tested by practical data from Beijing, showing that the proposed models are scientific and practicable. The study shows several conclusions. (1) When no subsidy policy is carried out, the regenerative electric heater and the air-sourced heat pump are not economically justified to replace the rural-household coal-fired boiler and coal-burning boiler and the public coal-fired boiler. (2) With the existing subsidy policy, the regenerative electric heater is economically justified to replace the rural-household coal-fired boiler, self-owned coal-burning boiler, and public coal-fired boiler, and the air-sourced heat pump can be the substituted for the rural-household coal-fired boiler. Under different wind–thermal-power ratios, the feasible intervals for the electricity price are respectively [47.12, 48.62], [44.31, 48.62], and [41.51, 48.62]. (3) Compared with the traditional coal-fired heating, wind-sourced electric heating contributes fewer pollutant emissions and more environmental benefits.